'Urf as a Method of Istinbath Islamic Law (Thoughts of Hasbi Ash-Shiddieqy with his Indonesian Fiqh) - Ramli, Ramli (Budapest International Research and Critics University, 2022)
The article examines the relation Tengku Muhammad Hasbi Ash-Shiddieqyis one of the most influential scholars in Islamic law reform in Indonesia, he brings local traditions ('urf/'adat) as the construction of Islamic Indonesian characteristic law. To construct Indonesian personality fiqh, Hasbi set off with 'urf/ traditions living in Indonesian society, he argued that every ‘urf/ customary law can be used as the postulateprovided that not conflict with the Shariah. It is not only 'urf/'customs of the Arabs, but also those who follow principles of egalitarian Islam, so that besides 'urf/'Arab customs can be used as the foundation of lawistinbat.